ANALISIS PENGARUH AUDIT INTERNAL DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD - Qonita Firdausi; Sunny Agung Kurniawan Kurniawan (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2025)
The purpose of this research was to comprehensively determine and analyze internal audit and whistleblowing system in the context of fraud prevention efforts. Whit a research design using qualitative descriptive analysis using a literature review approach. Data was collected in the form of journals or scientific articles as many as 10 articles from journal provider websites in 2019 - 2024. Based on the results of analysis of 10 articles, there are 6 articles stating that internal audit has a significant influence on fraud prevention efforts. This finding is supported by the results of data analysis from several studies which show a positive and significant correlation between the role of internal audit and fraud prevention efforts. Then 4 research articles do not explain the influence of internal audit. The result of the study in 10 article, there are 9 research article which state that the whistleblowing system has a positif influence of fraud prevention efforts.